Intelektualisme Cak Nur dan Sisi-Sisi Argumentatifnya - Amir Ahmad Nabil; Tasmin Abdul Rahman (Jurnal Peradaban, 2024)
The paper highlights the intellectual biography of Nurcholish Madjid (17 March 1939-29 August 2005) and his perennial ideas and influence in modern Islamic tradition and its lasting impact in Indonesia. Looking from its surface, the highly superior and exceptional works of Pak Nurcholish Madjid seems to invite his readers to argue and converse with him with absolute freedom without giving bother to any accusations or charges of anarchy. His writings that was full with philosophical arguments was constructed to inspired dialectical discussion and reasoning without ascribing to any established school of thought of the past. With his masterful works, it tries to challenges and draws our consciousness of the real force of intellectualism that was derived from scientific reflection and critical philosophical inquiry. The study is based on descriptive-qualitative approaches in the form of library and literature survey. The data were analysed by way of analytics, synthesis, biographical, historical and empirical techniques. The finding shows that Cak Nur’s intellectual strength was derived from the underlying empirical and historic method and framework in his effort to formulate and comprehend classical Islam and its intellectual tradition in term of its contextual and modern understanding and process.